Building safety into the conceptual design of complex systems. An aircraft systems perspective. - Jimeno Altelarrea, Sergio (Cranfield University, 2021)
Safety is a critical consideration during the design of an aircraft, as it constrains how primary functions of the system can be achieved. It is essential to include safety considerations from early design stages to avoid low-performance solutions or high costs associated with the substantial redesign that is commonly required when the system is found not to be safe at late stages of the design. Additionally, safety is a crucial element in the certification process of aircraft, which requires compliance with safety requirements to be demonstrated. Existing methods for safety assessment are limited in their ability to inform architectural decisions from early design stages. Current techniques often require large amounts of manual work and are not well integrated with other system engineering tools, which translates into increased time to synthesise and analyse architectures, thus reducing the number of alternative architectures that can be studied. This lack of timely safety assessment also results in a situation where safety models evolve at a different pace and become outdated with respect to the architecture definition, which limits their ability to provide valuable feedback. Within this context, the aim is to improve the efficiency and effectiveness of design for safety as an integral part of the systems architecting process. Three objectives are proposed to achieve the stated aim: automate and integrate the hazard assessment process with the systems architecting process; facilitate the interactive introduction of safety principles; and enable a faster assessment of safety and performance of architectures. The scope is restricted to the earlier (conceptual) design stages, the use of model-based systems engineering for systems architecting (RFLP paradigm) and steady-state models for rapid analysis. Regarding the first objective, an enabler to support the generation of safety requirements through hazard assessment was created. The enabler integrates the RFLP architecting process with the System-Theoretic Process Analysis to ensure consistency of the safety assessment and derived safety requirements more efficiently. Concerning the second objective, interactive enablers were developed to support the designer when synthesizing architectures featuring a combination of safety principles such as physical redundancy, functional redundancy, and containment. To ensure consistency and reduce the required amount of work for adding safety, these methods leverage the ability to trace dependencies within the logical view and between the RFLP domains of the architecture. As required by the third objective, methods were developed to automate substantial parts of the creation process of analysis models. In particular, the methods enable rapid obtention of models for Fault Tree Analysis and subsystem sizing considering advanced contextual information such as mission, environment, and system configurations. To evaluate this research, the methods were implemented into AirCADia Architect, an object-oriented architecting tool. The methods were verified and evaluated through their applications to two aircraft-related use cases. The first use case involves the wheel brake systems and the second one involves several subsystems. The results of this study were presented to a group of design specialists from a major airframe manufacturer for evaluation. The experts concluded that the proposed framework allows architects to define and analyse safe architectures faster, thus enabling a more effective and efficient design space exploration during conceptual design.
Keywords: Design for safety; aircraft conceptual design; model-based systems engineering (MBSE); systems-theoretic process analysis (STPA); safety principles; fault tree analysis (FTA); aircraft systems sizing